Spiracarneyella, a new carneyellid edrioasteroid from the Upper Ordovician (Katian) of Kentucky and Ohio and comments on carneyellid heterochrony. (May 2021) - Sumrall, Colin D.; Phelps, Daniel
Abstract: A new genus and species of carneyellid edrioasteroid, Spiracarneyella florencei n. gen. n. sp., is described from the Upper Ordovician (Kaitian) Point Pleasant Formation of northern Kentucky and southern Ohio. Spiracarneyella n. gen. is characterized by having all five ambulacra curving clockwise around the theca, having small node-bearing interambulacral plates in the distal interambulacra, and having the periproct placement slightly offset to the right side of the CD interambulacrum. The oral area of carneyellids evolved by paedomorphosis of the oral plates covering the mouth. The straight ambulacra of Cryptogoleus and the spiraling ambulacra of Spiracarneyella n. gen. evolved by paedomorphosis and peramorphosis, respectively. UUID: http://zoobank.org/79733c8f-0bc8-4e7e-8f77-8508f576755c